2012
DOI: 10.1038/oby.2011.80
|View full text |Cite
|
Sign up to set email alerts
|

The Women on the Move Through Activity and Nutrition (WOMAN) Study: Final 48‐Month Results

Abstract: The Women on the Move through Activity and Nutrition (WOMAN) study was designed to test whether a nonpharmacological intervention including qualitative and quantitative dietary changes to induce weight loss and increased physical activity levels would reduce blood triglyceride levels and number of low-density lipoprotein particles (LDL-P). Such decreases in lipoproteins and other risk factors could reduce or slow progression of subclinical cardiovascular disease (CVD). Study participants were randomized to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 38 publications
1
68
0
Order By: Relevance
“…In Lindstroem's study (42) significant improvements were seen at year 1 in fasting plasma glucose (0·2 v. 0·0 mmol/l), 2-h plasma glucose (0·9 v. 0·3 mmol/l), HbA1c (0·1 v. 0·1 %), serum total cholesterol to HDL-cholesterol ratio (0·4 v. 0·1), and serum TAG (0·2 v. 0·0 mmol/l) in the intervention group compared with the control group. Additionally, Kuller et al (40) found that systolic blood pressure (P = 0·048), LDL-cholesterol (P = 0·026), TAG (P = 0·92), insulin (P = 0·0001), glucose (P = 0·002) and HDL-cholesterol (P = 0·0001) developed significantly differently between the Health Education and the Lifestyle Change group. In the reviewed studies, the weight changes from baseline to weight loss ranged from −4·0 to −0·2 kg; in two studies they were not reported (38,41) .…”
Section: Effectiveness Of Energy Restriction and Macronutrient Composmentioning
confidence: 98%
See 4 more Smart Citations
“…In Lindstroem's study (42) significant improvements were seen at year 1 in fasting plasma glucose (0·2 v. 0·0 mmol/l), 2-h plasma glucose (0·9 v. 0·3 mmol/l), HbA1c (0·1 v. 0·1 %), serum total cholesterol to HDL-cholesterol ratio (0·4 v. 0·1), and serum TAG (0·2 v. 0·0 mmol/l) in the intervention group compared with the control group. Additionally, Kuller et al (40) found that systolic blood pressure (P = 0·048), LDL-cholesterol (P = 0·026), TAG (P = 0·92), insulin (P = 0·0001), glucose (P = 0·002) and HDL-cholesterol (P = 0·0001) developed significantly differently between the Health Education and the Lifestyle Change group. In the reviewed studies, the weight changes from baseline to weight loss ranged from −4·0 to −0·2 kg; in two studies they were not reported (38,41) .…”
Section: Effectiveness Of Energy Restriction and Macronutrient Composmentioning
confidence: 98%
“…Champagne et al (39) , Kuller et al (40) and Svetkey et al (43) included also overweight participants. In the weight loss period, all authors (36)(37)(38)(39)(40)(41)(42)(43) applied the reduction of energy intake to at least 5020·8-7531·2 kJ/d (37)(38)(39)(40)42,43) even to very low energy diet (41) and with ready-to-use formula (Optifast) (36) . The content of fat in the diet was taken into account especially by Wadden et al (37) , Milson et al (38) , Kuller et al (40) and Svetkey et al (43).…”
Section: Effectiveness Of Energy Restriction and Macronutrient Composmentioning
confidence: 99%
See 3 more Smart Citations